Fuzzy simple hierarchy analysis-based linguistic hedges in the selection of midsize luxury sport utility vehicles / Zamali Tarmudi and Ung L. Ling - Zamali Tarmudi; Ung L. Ling (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
The aim of this paper is to propose the use of the Fuzzy Simple Hierarchy Analysis (FSHA) using linguistic weight to deal with an ambiguous or vague multi-criteria datasets environment in the selection process. It focuses on vague multiple datasets evaluated based on fuzzy linguistic approaches. Linguistic hedges were used to cope with this issue during the evaluation process. The applicability and practicality of this proposed method was adopted to the selection of midsize luxury Sport Utility Vehicles (SUVs). Based on the analysis, it was found that this method is highly beneficial for the buyers in the sense that it can distinguish every single judgment made during the selection process clearly. It also offers a unique advantage and has successfully dealt with diversified and ill-defined parameters in terms of input data criterion. Thus, this method can assist potential buyers to make their decision in a simple and systematic manner.